2019
DOI: 10.3390/app9112187
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Emission Monitoring of Fatigue Crack Growth in Mooring Chains

Abstract: Offshore installations are subject to perpetual fatigue loading and are usually very hard to inspect. Close visual inspection from the turret is usually too hazardous for divers and is not possible with remotely operated vehicles (ROVs) because of the limited access. Conventional nondestructive techniques (NDTs) have been used in the past to carry out inspections of mooring chains, floating production storage and offloading systems (FPSOs), and other platforms. Although these have been successful at detecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The current offshore inspection methods face several issues that hinder their effectiveness and efficiency. One of the main issues is the reliance on traditional inspection techniques, such as visual inspection and nondestructive testing (NDT), which are often time-consuming, costly, and limited in their ability to access hard-to-reach areas [3]. These methods require human intervention and are subject to human error, which makes them less reliable [4].…”
Section: Challenges Of Traditional Offshore Inspection Methodsmentioning
confidence: 99%
“…The current offshore inspection methods face several issues that hinder their effectiveness and efficiency. One of the main issues is the reliance on traditional inspection techniques, such as visual inspection and nondestructive testing (NDT), which are often time-consuming, costly, and limited in their ability to access hard-to-reach areas [3]. These methods require human intervention and are subject to human error, which makes them less reliable [4].…”
Section: Challenges Of Traditional Offshore Inspection Methodsmentioning
confidence: 99%
“…The topic of the acoustic ultrasound emissions study for monitoring of fatigue crack growth in mooring chains [12] and for rail defect detection [13] is faced respectively by Angulo et al and Shi et al, with very interesting results. Dobrzychi et al applies the acoustic emissions technique to epoxy resin electrical treeing study [14].…”
Section: Modelling Simulation and Data Analysis In Acoustical Problemsmentioning
confidence: 99%
“…The foremost mooring-line monitoring technologies include sonar probes, inclinometers, load cells, and fiberoptic sensors [ 9 , 10 , 11 ]. Some authors have also suggested ultrasonic guided waves and acoustic emissions as potential solutions.…”
Section: Introductionmentioning
confidence: 99%